Plasma asprosin, CCDC80 and ANGPTL4 levels are associated with metabolic and cardiovascular risk in patients with inflammatory bowel disease - Wang, Hao-Hua; Luo, Wan-Ying; Lin, Min; Li, Xiao-Jing; Xiang, Guang-Da; d Triganti, Silvia (Physiological research, 2021)
Asprosin, coiled-coil domain-containing 80(CCDC80) and angiopoietin-like 4(ANGPTL4) are newly discovered adipocytokine that affects glucose tolerance, insulin resistance and cardiovascular diseases. The goal of this study was to investigate if a relationship exists among asprosin, CCDC80 and ANGPTL4 and inflammatory bowel disease (IBD). Fifty subjects with newly diagnosed IBD and fifty healthy individuals were enrolled. Patients were treated with standard therapies for 3 months. Plasma asprosin, CCDC80 and ANGPTL4 levels were measured with enzyme-linked immunosorbent assay. High resolution ultrasound was used to measure brachial artery diameter at rest, after reactive hyperemia (flow-mediated dilation, FMD) and after sublingual glyceryltrinitrate. Compare with healthy individuals, plasma CCDC80, erythrocyte sedi¬mentation rate (ESR), C-reactive protein (CRP) levels and homeostasis model assessment of insulin resistance (HOMA-IR) were significantly higher (p < 0.05, respectively), whereas plasma asprosin, ANGPTL4 levels and FMD were significantly lower in both UC and CD patients (p < 0.05). Plasma CCDC80 levels were significantly higher in patients with CD (p < 0.05), while plasma asprosin and ANGPTL4 levels were lower (pP < 0.05) as compared with those in patients with UC. Standard therapies increased plasma asprosin, ANGPTL4 levels and FMD in both UC and CD (p < 0.05), UC and CD patientswhile decreased plasma CCDC80, ESR, CRP levels and HOMA-IR (p < 0.05). The changes in HOMA-IR and FMD were correlated with the changes in plasma asprosin, CCDC80 and ANGPTL4 levels over the study period (p < 0.05). Plasma asprosin, CCDC80 and ANGPTL4 levels may be applied as a significant marker for early stage of insulin resistance and atherosclerosis in IBD, especially of CD.